Revising the Pragmatics Profile of Everyday Communication Skills for traumatic brain injury: An international Delphi study - Tomlin, Lily; Smidt, Andy; Bogart, Elise (International journal of language & communication disorders, 2024)
Background Assessment tools that assess pragmatic skills in adults with a mild‐severe traumatic brain injury (TBI) are hard to access, not person‐centred and have a high risk of clinician bias. The Pragmatics Profile is an informant report tool that was originally designed to assess pragmatic skills in people with a developmental disability. Aims The aim of this study was to seek consensus from a panel of experts and create a version of the Pragmatics Profile for the TBI population. Methods and Procedures A three‐round modified Delphi methodology panel of 13 experts were invited to comment anonymously on the suitability of each question from the Pragmatics Profile modified for those with TBI until ≥ 80% agreement was reached. Outcomes and Results The Pragmatics Profile (TBI) included 66 questions that achieved consensus after three rounds of the Delphi panel. Qualitative analysis illuminated themes relating to adults with TBI and the need to include contextual factors. Conclusions and Implications The outcome of this project was a revised version of the Pragmatics Profile which is suitable for adults with a mild‐severe TBI, informed by experts and freely available online. Future research exploring the tool's utility and acceptability is the next step in its evaluation. WHAT THIS PAPER ADDS What is already known on this subject Assessment of the everyday functional use of language is challenging but vital. This is particularly true for those who have traumatic brain injury (TBI) where the communication outcomes can be highly variable and may include difficulties with conversational turn‐taking, topic maintenance and reading social cues. There are limited tools available to clinicians and those tend to be rating scales or checklists which have a high risk of clinician bias. Available tools have a limited ability to capture the individual's personal social communication goals. What this paper adds to existing knowledge This study created an online Pragmatics Profile (PP) for TBI based on experts’ opinions. This paper details the themes that emerged during the process of revising the PP for those with TBI. What are the potential or actual clinical implications of this work? The PP‐TBI adds to the toolkit for speech and language therapists working with people with TBI. It meets recent recommendations in the literature to create an interview‐based tool. The versatility of an online tool combined with revised input from a panel of experts increases the likelihood that clinicians will utilise this tool. Given the long‐term use of the original PP by clinicians for almost 30 years and a focus on personalised care, the format and approach are also likely to be acceptable to clinicians.